PENGARUH PENDIDIKAN KESEHATAN TENTANG RESUSITASI JANTUNG PARU (RJP) TERHADAP SIKAP NON PENDIDIK PADA KASUS MENGENAI HENTI JANTUNG - Ahmad Arifin; Budi Rustandi; A. Pratama (PROSIDING SIMPOSIUM KESEHATAN NASIONAL, 2022)
Background: Health education about BHD consisting of CPR for rescuers is the main thing. Research Objectives: To determine the effect of health education about CPR on the attitude of non-educators in cases of cardiac arrest. Methodology: pre-experimental research designpre- and post-test without-control. The sample size is 18 people. Results: From 18 respondents showed negative first aid attitudes beforebeing given health education about CPR as many as 13 respondents (72.2%) positive first aid attitudes after being given health education about CPR as many as 17 respondents (94.4%). Conclusion: Based on the results of the study, it showed that there was an effect of CPRhealth education on the attitude of non-teaching staff with cases of cardiac arrest.